Africa agriculture transformation scorecard performance and lessons for Zambia - Sikombe, D.; Mbewe, C.; Matchaya, Greenwell C.; Nhemachena, Charles; Nhlengethwa, Sibusiso (Regional Strategic Analysis and Knowledge Support System for Southern Africa, 2019)
To ensure that the Biannual Review (BR) process embodies the CAADP/Malabo principles, particularly focusing on Commitment 7 (enhancing mutual accountability for actions and results) of the Malabo Declaration, the African Union Commission (AUC) launched the Inaugural Biennial Review reporting mechanism on the implementation of the Malabo commitments. In line with the above continental commitment on mutual accountability, Zambia implemented the BR process to track progress in the implementation of the CAADP agenda, particularly the 2014 Malabo commitments. The process provided a platform for stakeholders in the agriculture sector (the public sector, private sector, development partners, civil society organizations, academia, and research institutions) to hold each other mutually accountable on both financial and nonfinancial commitments they made toward common development goals for the agriculture sector. The BR process also helped provide a platform for agriculture sector stakeholders to learn from each other (peer learning). The Biennial Review Report (BRR) fosters alignment, harmonization, and coordination among multisectoral efforts and multi-institutional platforms for peer review, mutual learning, and accountability. The objective of this brief is to analyze Zambia's performance and discuss lessons from the implementation of the inaugural CAADP BR mechanism.